EU protected area network did not prevent a country wide population decline in a threatened grassland bird - João P. Silva; Ricardo Correia; Hany Alonso; Ricardo C. Martins; Marcello D’Amico; Ana Delgado; Hugo Sampaio; Carlos Godinho; Francisco Moreira (PeerJ, 2018)
Background Few studies have assessed the effectiveness of the Protected Area networks on the conservation status of target species. Here, we assess the effectiveness of the Portuguese Natura 2000 (the European Union network of protected areas) in maintaining a species included in the Annex I of the Bird Directive, namely the population of a priority farmland bird, the little bustard Tetrax tetrax. Methods We measured the effectiveness of the Natura 2000 by comparing population trends across time (2003–2006 and 2016) in 51 areas, 21 of which within 12 Special Protection Areas (SPA) that were mostly designated for farmland bird conservation and another 30 areas without EU protection. Results Overall, the national population is estimated to have declined 49% over the last 10–14 years. This loss was found to be proportionally larger outside SPA (64% decline) compared to losses within SPA (25% decline). However, the absolute male density decline was significantly larger within SPA . Discussion In spite of holding higher population densities and having prevented habitat loss, we conclude that Natura 2000 was not effective in buffering against the overall bustard population decline. Results show that the mere designation of SPA in farmland is not enough to secure species populations and has to be combined with agricultural policies and investment to maintain not only habitat availability but also habitat quality.